West meets east: Understanding managerial incentives in Chinese SOEs - Qingquan Xin; Anze Bao; Fang Hu (China Journal of Accounting Research, 2019)
State-owned enterprises (SOE) are essentially extensions of the government and are therefore responsible for multi-task objectives. The incentive system for SOE managers consists of both monetary compensation and promotion within the bureaucratic system. Political promotion is key to understanding the incentives of SOE managers. In the reform and opening up era, SOEs have been reformed and exposed to political and market forces. The design of incentive systems for SOE managers has thus become complicated and challenging. Our study provides important implications for this key issue of SOE reform.
Keywords: 650; Bureaucratic hierarchy; Managerial incentives; Political promotion; SOE